Higher prevalence of seizure activity in a small population of atopic dogs: a retrospective breed‐ and age‐matched study. Issue 2 (27th November 2020) - Herrmann, Ina; Kradischnig, Clarissa; Skor, Ondrej; Pakozdy, Akos; Panakova, Lucia
Abstract : Background: Atopic dermatitis (AD) is considered to be a systemic disease in people shown to have an association with epilepsy. However, so far, no data about the association of epilepsy and atopy have been reported in dogs. Objectives: Given the homology between human and canine AD, and the increased incidence of epilepsy in atopic people, we investigated the association between AD and seizure‐associated activity in a small canine population. Animals: We included 34 atopic dogs and 34 breed‐ and age range‐matched nonatopic dogs. Methods and materials: We investigated the association between canine AD and signs of seizures in a retrospective, breed‐ and age range‐matched, case‐controlled study. Dog owners were interviewed using a standardized questionnaire. The presence or absence of signs of seizure activity and possible comorbidities were questioned. Results: Seven of the 34 atopic dogs also suffered from seizure activity. By contrast, only one dog affected with seizure signs could be identified among the 34 nonatopic dogs. Atopic dermatitis was associated with a higher frequency of seizure activity (McNemar test, P = 0.035; one‐sided) and atopic dogs had a higher odds ratio to develop seizures [(95% CI) 7 (0.9–56.9)] compared to the age‐ and breed‐matched nonatopic control group. No other comorbidities were detected. Conclusion and clinical importance: In our small retrospective study, we observed an increased prevalence of seizure activity in the atopic dog population. Further larger and prospective studies are needed to confirm these results. Abstract : Background – Atopic dermatitis (AD) is considered to be a systemic disease in people shown to have an association with epilepsy. However, so far, no data about the association of epilepsy and atopy have been reported in dogs. Objectives – Given the homology between human and canine AD, and the increased incidence of epilepsy in atopic people, we investigated the association between AD and seizure‐associated activity in a small canine population. Conclusion and clinical importance – In our small retrospective study, we observed an increased prevalence of seizure activity in the atopic dog population. Further larger and prospective studies are needed to confirm these results. Résumé: Contexte: La dermatite atopique (AD) est considérée comme une maladie systémique chez l'homme ayant montré une association avec l'épilepsie. Cependant, à ce jour, aucune donnée n'existe chez le chien sur une association entre épilepsie et atopie. Objectifs: Etant donné l'homologie entre AD humaine et canine, et l'incidence croissante de l'épilepsie chez l'homme atopique, nous étudions l'association entre AD et crise d'épilepsie associée à l'activité dans une population canine. Sujets: Nous incluons 34 chiens atopiques diagnostiqués par notre service de dermatologie et 34 chiens non atopiques d'âge correspondant. Méthodes: Nous étudions l'association entre chien AD et les signes de crise d'épilepsie dans une étude rétrospective, contrôlée et associée par âge et race. Les propriétaires de chiens ont répondu à un questionnaire standard. La présence ou l'absence de signes de crise d'épilepsie et les comorbidités possibles ont été demandées. Résultats: Sept des 34 chiens atopiques soufraient également de crises d'épilepsie. Au contraire, seulement un chien atteint de signes d'épilepsie a pu être identifié parmi les 34 chiens non atopiques. La dermatite atopique a été associée avec une fréquence plus élevée d'épilepsie (McNemar test, P = 0.035; one‐sided) et les chiens atopique savaient un odd ratio plus élevé à développer des crises d'épilepsie [(95% CI) 7 (0.9–56.9)] comparé au groupe contrôle non atopique associé par âge et par race. Aucune autre comorbidité n'a été détectée. Conclusion et importance clinique: Dans notre petite étude rétrospective nous observons une augmentation de la prévalence des signes d'épilepsie au sein de la population canine atopique. Des études prospectives à plus large échelle sont nécessaires pour confirmer ces résultats. Resumen: Introducción: la dermatitis atópica (AD) se considera una enfermedad sistémica en personas que se ha demostrado que tienen una asociación con la epilepsia. Sin embargo, hasta el momento, no se han reconocido una la asociación entre la epilepsia y la atopia en perros. Objetivos: dada la homología entre la AD humana y canina y la mayor incidencia de epilepsia en personas atópicas, investigamos la asociación entre la AD y la actividad asociada a convulsiones en la población canina. Animales: incluimos 34 perros atópicos diagnosticados por nuestro servicio de dermatología y 34 perros no atópicos de la misma raza y rango de edad. Métodos: investigamos la asociación entre la AD canina y los signos de convulsiones en un estudio de casos y controles retrospectivo, emparejado por razas y rangos de edad. Los dueños de perros fueron entrevistados mediante un cuestionario estandarizado. Se cuestionó la presencia o ausencia de signos de actividad convulsiva y posibles comorbilidades. Resultados: siete de los 34 perros atópicos también sufrieron convulsiones. Por el contrario, solo se pudo identificar un perro afectado con signos de convulsiones entre los 34 perros no atópicos. La dermatitis atópica se asoció con una mayor frecuencia de actividad convulsiva (prueba de McNemar, P = 0, 035; unilateral) y los perros atópicos tenían una relación de probabilidad más alta para desarrollar convulsiones [(IC del 95%) 7 (0, 9‐56, 9)] en comparación con el grupo control no atópico emparejado por edad y raza. No se detectaron otras comorbilidades. Conclusión e importancia clínica: en nuestro pequeño estudio retrospectivo, observamos una mayor prevalencia de actividad convulsiva en la población de perros atópicos. Se necesitan estudios prospectivos más amplios para confirmar estos resultados. Zusammenfassung: Hintergrund: Die atopische Dermatitis (AD) gilt als systemische Erkrankung beim Menschen, bei der ein Zusammenhang mit Epilepsie gezeigt werden konnte. Es konnten allerdings bis jetzt keine Daten über einen Zusammenhang zwischen Epilepsie und Atopie bei Hunden publiziert werden. Ziele: Aufgrund der bestehenden Homologie zwischen der AD des Menschen und des Hundes und des zunehmenden Auftretens von Epilepsie bei atopischen Menschen, untersuchten wir den Zusammenhang zwischen AD und dem Auftreten eines Anfallsgeschehens in der Hundepopulation. Tiere: Wir inkludierten 34 atopische Hunde, die durch unser Dermatologie Service diagnostiziert worden waren und 34 Rasse‐ und Alters‐angepasste nicht atopische Hunde. Methoden: Wir untersuchten den Zusammenhang zwischen der AD des Hundes und Anzeichen von Anfällen in einer retrospektiven, an Rasse‐ und Alter‐angepassten Fall‐Kontroll‐Studie. HundebesitzerInnen wurden mittels standardisiertem Fragebogen interviewed. Es wurde nach dem Auftreten oder dem Nicht‐Auftreten von Anfallsaktivitäten und möglichen Begleiterkrankungen gefragt. Ergebnisse: Sieben von 34 atopischen Hunden litten auch an Anfällen. Im Gegensatz dazu konnte nur ein Hund mit Anfällen aus der Gruppe der 34 nicht‐atopischen Hunde identifiziert werden. Die atopische Dermatitis trat im Zusammenhang mit einer höheren Frequenz an Anfällen auf (McNemar Test, P = 0, 035; einseitig) und atopische Hunde zeigten ein höheres Quotenverhältnis Anfälle zu entwickeln [(95% CI) 7 (0, 9‐56, 9)] im Vergleich zur Alters‐ und Rasse‐angepassten nicht‐atopischen Kontrollgruppe. Es wurden keine weiteren Begleiterkrankungen festgestellt. Schlussfolgerung und klinische Bedeutung: In unserer kleinen retrospektiven Studie konnten wir ein zunehmendes Anfallsgeschehen in der atopischen Hundepopulation beobachten. Es sind weitere große und prospektive Studien nötig, um diese Ergebnisse zu bestätigen. 概要: 背景: 特应性皮炎(AD)被认为是可以引起人发生癫痫的全身性疾病。然而, 到目前为止, 尚未有报告犬特应性癫痫的资料。 目的: 鉴于人和犬AD之间的一致性, 以及特应性人群中癫痫的发生率增加, 我们研究了犬群中AD与癫痫发作之间的相关性。 动物: 纳入由我们的皮肤病服务机构诊断出的34只特应性犬, 以及34只品种和年龄范围匹配的非特应性犬。 方法: 在这项回顾性、品种和年龄范围匹配的病例对照研究中, 我们研究了犬AD与癫痫体征之间的相关性。采用标准化问卷对犬主人进行访谈。询问是否存在癫痫发作体征和可能的并发症。 结果: 34只特应性犬中有7只同时出现癫痫发作。相比之下, 在34只非特应性犬中, 仅可确定1只犬有癫痫体征。与年龄和品种匹配的非特应性对照组相比, 特应性皮炎与癫痫发作频率较高相关 (McNemar检验, P = 0.035;单侧), 特应性犬发生癫痫的比率[(95%CI)7(0.9‐56.9)]更高。未检测到其他并发症。 结论和临床重要性: 在我们的小型回顾性研究中, 我们观察到特应性犬群中癫痫发作率增加。需要进一步的更大规模和前瞻性研究来证实这些结果。 要約: 背景: アトピー性皮膚炎 (AD) は、てんかんとの関連が示されている人々の全身性疾患であると考えられている。しかし、これまでのところ、てんかんとアトピーの関連についてのデータは犬で報告されていない。 目的: 本研究の目的は、人間と犬のADの相同性、およびアトピー性皮膚炎の発生率の増加を考慮して、AD及び犬の集団における発作関連活動との関連を調査することであった。 供試動物: 皮膚科サービスによって診断された34頭のアトピー犬および品種、年齢範囲が一致する34頭の非アトピー犬を本研究に包含した。 方法: 犬ADと発作の兆候との関連を、遡及的、品種および年齢範囲を一致させた、症例対照研究によって調査した。犬の飼い主は、標準化された質問票を使用してインタビューを受けた。発作活動の兆候の有無及び併存疾患の可能性が疑問視された。 結果: 34頭のアトピー犬のうち7頭も発作活動に苦しんでいた。対照的に、34頭の非アトピー犬の中で発作兆候に冒された1頭の犬だけが識別できた。アトピー性皮膚炎は発作活動の頻度が高く (マクネマー検定、P = 0.035;片側) 、アトピー犬は年齢及び品種が一致する非アトピー性対照群と比較して発作を発症するオッズ比が高かった[(95%CI)7(0.9–56.9)]。他の併存疾患は検出されなかった。 結論と臨床的重要性: 我々の小規模後ろ向き研究では、アトピー犬集団における発作活動の有病率の増加が観察された。本研究結果を確認するには、さらなる大規模前向き研究が必要である。 Resumo: Contexto: A dermatite atópica (DA) é considerada uma doença sistêmica em pessoas com associação com epilepsia. No entanto, até o momento, nenhum dado sobre a associação de epilepsia e atopia foi relatado em cães. Objetivos: Dada a homologia entre a DA humana e canina, e o aumento da incidência de epilepsia em pessoas atópicas, investigamos a associação entre a DA e a atividade associada a convulsões na população canina. Animais: Incluímos 34 cães atópicos diagnosticados por nosso serviço de dermatologia e 34 cães não atópicos de raça e faixa etária correspondentes. Métodos: Nós investigamos a associação entre DA canina e sinais de convulsões em um estudo de caso‐controle retrospectivo, pareado por raça e idade. Os proprietários de cães foram entrevistados por meio de um questionário padronizado. Questionou‐se a presença ou ausência de sinais de atividade convulsiva e possíveis comorbidades. Resultados: Sete dos 34 cães atópicos também sofreram convulsões. Em contraste, apenas um cão afetado com sinais de convulsão pôde ser identificado entre os 34 cães não atópicos. A dermatite atópica foi associada a uma maior frequência de atividade convulsiva (teste de McNemar, P =0, 035; unilateral) e os cães atópicos tiveram uma maior razão de chances de desenvolver convulsões [(IC 95%) 7 (0, 9‐56, 9)] em comparação com o grupo de controle não atópico de mesma idade e raça. Nenhuma outra comorbidade foi detectada. Conclusão e importância clínica: Em nosso pequeno estudo retrospectivo, observamos um aumento na prevalência de atividade convulsiva na população canina atópica. Mais estudos maiores e prospectivos são necessários para confirmar esses resultados.